2022
DOI: 10.2217/fon-2022-0337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Evaluation of PSOX, DOF and SOX Regimens as Neoadjuvant Chemotherapy for Advanced Gastric Cancer

Abstract: Aim: To explore the efficacy and safety of paclitaxel+oxaliplatin+S-1 (PSOX), docetaxel+oxaliplatin+fluorouracil (DOF) and oxaliplatin+S-1 (SOX) regimens as neoadjuvant chemotherapy for advanced gastric cancer (GC). Methods: A retrospective analysis was used in 306 patients with GC who underwent neoadjuvant chemotherapy, consisting of 102 from the PSOX group, 100 from the DOF group and 104 from the SOX group. Results: The total effective rates and disease control rates for the PSOX, DOF and SOX groups were 31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results showed that there was no significant difference in the incidence of adverse events among p‐SOX group, DOF group, and SOX group ( p > 0.05). Therefore, P‐SOX regimen has excellent safety and efficacy, and is expected to become a first‐line neoadjuvant chemotherapy regimen for patients with gastric cancer 37 . In conclusion, nab‐paclitaxel combined with oxaliplatin and S‐1 has a certain positive significance in the treatment of advanced gastric cancer, and is expected to become a new chemotherapy regimen for advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that there was no significant difference in the incidence of adverse events among p‐SOX group, DOF group, and SOX group ( p > 0.05). Therefore, P‐SOX regimen has excellent safety and efficacy, and is expected to become a first‐line neoadjuvant chemotherapy regimen for patients with gastric cancer 37 . In conclusion, nab‐paclitaxel combined with oxaliplatin and S‐1 has a certain positive significance in the treatment of advanced gastric cancer, and is expected to become a new chemotherapy regimen for advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 96%